Thermodynamic Optimization of Stored Liquid–A Holistic Approach - Rakshit, D.; Narayanaswamy, Ramesh; Thiagarajan, K. (IIT Kharagpur, 2013)
A holistic approach was adopted to thermally optimize a storage container that was partially filled with liquid (water). The ullage region above the liquid was composed of water vapor and air. In this optimization two symbiotic physical parameters that influence the thermal performance of thestorage container, namely interfacial mass transfer and the entropy generated by the system, were simultaneously considered. The optimization proposed a set of temperatures for two different filling levels that would maximize the interfacial mass transfer by keeping the entropy generated bythe system at its minimum possible level. The mass transfer estimation involved the determination of (i) liquid-vapor interfacial temperature, (ii) fractional concentration of the evaporating liquid present in the gaseous state, and (iii) surface area of the liquid-vapor interface. The entropy of the system was estimated separately by considering the entropy of the diabatic saturated liquid and the ullage vapor. This was followed by the composition of a synergistically considered objective function based on the penalty involved in deviation from the individual optima. Thus, a holistic optimum was determined. It was seen that stored liquids showed a better Second Law efficiency for open containers as compared to itsclosed counterpart. The main influencing factor that contributes to this type of optimum is the roof condensation that occurred for closed containers at 50% filling level.